Fetal Binocular Distance in Sudanese, Sono-graphic Study - Fadol, Ammar Mohammed Ali Mohammed; Ali, Qurashi Mohammed; Hamza, Abbas Elnour (مجلة الجزيرة للعلوم الصحية; مجلد 17 عدد 1 (2021), 2022)
Background: Recent developments in fetal ultrasound technology represent effective tools for gestation age (GA) estimation and screening of abnormalities in fetal development. Fetal orbital measurements as well as binocular distance (BOD) not performed routinely during obstetrical sono-graphy, although not very popular, can aid in GA and fetal weight (FW) estimation. Objectives: The aim of this study was to construct reference ranges for fetal BOD in Sudan, and to evaluate the correlations of BOD with GA, FW, sex, and other common biometric measurements. Subjects and methods: In this prospective, descriptive, cross sectional study, a total of 385 Sudanese healthy pregnant ladies with regular menstrual cycle and certainty about the time of the last menstrual period and age ranged of 16 – 44 years, within 14 to 41 weeks of gestation; individuals underwent routine sono-graphy were examined at obstetrics and gynecology clinic in Omdurman, Sudan. Normal pregnancies of viable singleton with good sono-graphic visualization of the fetus face were included in this study. Moreover, descriptive statistics, linear regression models were employed by using SPSS version 22 (SPSS Inc, IBM) at 95% confidence intervals. Results: Fetal BOD range (15 - 64 mm),mean (40.1 ± 10.7 mm). Linear growth functions were significant between BOD with GA (r=0.930, P < 0.0001), FW (r=0.801, P < 0.0001) and other common fetal biometric parameters such as biparietal diameter (r=0.935, P < 0.0001), head circumference (r=0.879, P < 0.0001), femur length (r=0.939, P < 0.0001) and abdominal circumference (r=0.701, P < 0.0001). Furthermore, BOD showed significant correlation with both fetal sex (P = 0.021) and mother’s tribe (P = 0.023). Conclusion: BOD significantly increased with increasing GA. Reference ranges developed in the present study will enable accurate evaluation of menstrual age throughout pregnancy. However, nomograms of BOD for Sudanese fetuses of 14–41 weeks gestation have been constructed.